NEW APPROACHES IN SOCIAL WELL- BEING STUDIES - Dunaeva, Victoria (PEOPLE: International Journal of Social Sciences, 2018)
In last decades it is possible to observe popularity the concept of well-being, which present meaningful and satisfied life for personality, special kind of attitude (to oneself and environment). Well-being is often associated with physical vitality, mental activity, social support and satisfaction, self-realization both in personal and professional fields. It is considered as an alternative of negative way of thinking, destructive defensive mechanisms and inappropriate style of living. Social well-being as significant part of well-being is connected with our relations with others and our feeling of security related to the environment we live in. In my presentation I would like to present new contemporary approaches in studies of social well-being. It is most related to the quality of our existence on social level, our capacity to find out own place in the environment independently of economic and social factors.